Perbedaan Tingkat Stres Antara Perawat Instalasi Gawat Darurat dan Perawat Intensive Care Unit Umum di RSU Santo Antonius Kota Pontianak - Elnisa Asritamara; Vip Paramarta; Kosasih Kosasih (Universitas Pahlawan Tuanku Tambusai, 2026)
Stress is a physical and emotional response of the body triggered by various sources of pressure. This condition is commonly experienced by healthcare workers in hospital settings, particularly nurses assigned to the Emergency Department (ED) and General Intensive Care Unit (ICU). Occupational stress among nurses may stem from excessive workloads, difficulties in communicating with fellow staff, challenges in managing critically ill patients, insufficient personal preparedness, uncertainty in clinical decision-making regarding medication, and problems arising from patients or their families. The level of work-related stress experienced by nurses can be classified into three categories: low, moderate, and high. This study aimed to determine whether a significant difference exists in stress levels between ED nurses and General ICU nurses at Santo Antonius General Hospital in Pontianak. An observational analytic method with a cross-sectional design was employed, with ED and General ICU nurses as the independent variables and stress level as the dependent variable. A total of 27 ED nurses and 31 ICU nurses were selected as research subjects using purposive sampling based on predetermined inclusion and exclusion criteria. The Mann-Whitney test conducted using SPSS 20.0 showed ρ value = 0,21, indicating that there was no statistically significant difference in stress levels between ED nurses and General ICU nurses at Santo Antonius General Hospital in Pontianak. Based on these findings, this study recommends that both ED and General ICU nurses implement appropriate stress management strategies to minimize the impact of occupational stress. Keywords: stress level, emergency department nurses, General ICU nurses, hospital.